De la extrema medianía, la honestísima deshonestidad y otros pecadillos del honnête homme (2014)
This paper approach the matter of honnêteté theory, especially following the text of Nicholas Faret The honest man or art to please the court and focuses on two fundamental points that support this theory: half points and pretense. Secondarily, thinks about the relationship and presence of this polite behavior theory in two works of Marquis de Sade: Juliet or vice amply rewarded and Justine or the misfortunes of virtue.